Causal Elements of Locus of Control as Predictors of English Language Achievement among Secondary School students in Kisumu East Sub-county, Kisumu County Kenya - Atieno, Hawa Rabong'o (JOOUST, 2020)
The impact of English as a global language in many spheres of international life has been quite rapid, and with English becoming the world's foremost lingua franca, the pressure to improve English language education has been steadily increasing internationally. Similarly, the language of instruction in Kenyan secondary schools has, over the years, been English. Thus, students' proficiency in English goes a long way in determining student academic achievement. There is relatively poor achievement in English language in Kisumu East Sub-County. However, very scanty research is available on the possible influence of causal elements of locus of control and achievement in English language. The purpose of the study was to investigate the relationship between causal elements of locus of control and English language achievement among secondary school students in Kisumu East Sub-County. The objectives of the study were; to establish the relationship between cognitive ability and achievement in English language among secondary school students in Kisumu East Sub-County, to examine the relationship between effort and achievement in English language among secondary school students in Kisumu East Sub-County, to determine the relationship between task difficulty and achievement in English language among secondary school students in Kisumu East Sub-County and to find out the relationship between selected significant others and achievement in English language among secondary school students in Kisumu East Sub-County. The study was guided by Lev Vygotsky's Social Development Theory and Urie Bronfenbrenner's Ecological System Theory. The study employed Sequential Explanatory design within mixed methods approach. Target population comprised 6000 students drawn from 19 secondary schools in Kisumu East Sub-County. The study sample included 600 form 3 students. Stratified sampling and simple random sampling techniques were used to draw the samples. Data collection instruments were Questionnaires, Focus Group Discussion and English Language Achievement Test. The instruments were validated by engaging research supervisors to check and assess the frequency of error and accuracy. Reliability was ascertained using Cronbach's alpha and a reliability coefficient of alpha above 0.7 was obtained. Collected data was analyzed using SPSS computer software version 22. Quantitative data was analyzed using descriptive statistics and inferential statistics such as Pearson Correlation while qualitative data was analyzed thematically. Regression analysis revealed that causal elements of locus of control accounted for 9.6% (R2= .096) of variation in English language achievement among secondary school students in Kisumu East Sub county with cognitive ability making the greatest contribution at B 0.381. The study findings indicated that cognitive abilities can positively influence students' achievement in English language, students efforts is strongly related to their learning and achievement in English language, the difficulty of a task is determined by the learner characteristic and task type, and an increase in task difficulty leads to a decrease in achievement in English language, teaching/learning material sources significantly increase students' achievement in English language by supporting student learning, teaching learning methods used can positively or negatively influence achievement in English language, peer group has significant influence on academic achievement in English language. One of the recommendations was that teacher counselors to organize structured guidance programs meant to enhance personal student effort in the students' academics.